2021
DOI: 10.3390/en14217199
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Liquid Digestate as the Sole Nutrient Source for Floating Hydroponic Cultivation of Baby Lettuce (Lactuca sativa) in Greenhouses

Abstract: Sustainable agriculture relies on replacing fossil-based mineral fertilizers, which are highly cost-energetic to produce, and demand extensive use of scarce natural resources. Today, agronomic practices within the concept of circular economy are emerging and, as such, the exploitation of digestate as a biofertilizer and soil amender is extensively investigated. This study aimed at evaluating the agronomic potential of liquid digestate as the sole nutrient source for hydroponic cultivation of baby lettuce in gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The reduction in micronutrients in the lettuce leaves could likely be ascribed to their lower solubility due to the higher digestate pH compared to the soil one (Table S1), as reported by Olszyk et al [68], who observed a decrease in Fe, Mn, and Zn concentrations, mainly, in lettuce plants grown in the presence of several biochars as amendments. Similarly, a reduction in Fe uptake was detected in baby leaf lettuce under different digestate [69,70]. The addition of a low Cu concentration (M+Cu and D+Cu) caused in the plant leaves a twofold increase in Cu uptake with respect to the control (S).…”
Section: Macro-and Micro-nutrient Content In Lettuce Plantsmentioning
confidence: 77%
“…The reduction in micronutrients in the lettuce leaves could likely be ascribed to their lower solubility due to the higher digestate pH compared to the soil one (Table S1), as reported by Olszyk et al [68], who observed a decrease in Fe, Mn, and Zn concentrations, mainly, in lettuce plants grown in the presence of several biochars as amendments. Similarly, a reduction in Fe uptake was detected in baby leaf lettuce under different digestate [69,70]. The addition of a low Cu concentration (M+Cu and D+Cu) caused in the plant leaves a twofold increase in Cu uptake with respect to the control (S).…”
Section: Macro-and Micro-nutrient Content In Lettuce Plantsmentioning
confidence: 77%
“…In addition, an important research need could be the development of varieties that pertain to this cultivation method in Greece and also to resolve issues with regards to waterborne diseases. A specific type of such technologies could be new ways for valorizing recycled water in hydroponics, such as the combination of aquaponics with plant growing in greenhouses [53], or the use of alternative substrates in the framework of a circular economy [54], both of which are being investigated in Greece. This would also allow for the better monitoring of water quality, thus decreasing the danger for waterborne diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Reuland et al [25] stated that the digestate liquid provided better conditions for plant growth than unseparated digestate. In addition, Ntinas et al [26] demonstrated the efficient application of digestate liquid from livestock manure as a fertilizer for the hydroponic cultivation of baby lettuce grown in a greenhouse using a floating system. Similarly, Levin et al [27] confirmed that the liquid fraction from cow manure exhibited better fertilization performance for cucumber due to the fast release of nutrients (i.e., nitrogen) to the plants.…”
Section: Materials Flow Of An Anaerobic Digestion System Under the Si...mentioning
confidence: 99%